SISTEM E-FILING DAN KESADARAN WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK DENGAN RELAWAN PAJAK SEBABAGAI VARIABEL MODERATING - Prihatini, Marcelina; Kusumawati, Nugrahini; Amyati, Amyati (Universitas Bina Bangsa, 2024)
Taxpayers are compliant with taxation if they know and carry out their obligations. The lower taxpayer compliance, the lower tax revenues will be. Taxpayer awareness of paying and reporting their taxes correctly and clearly, supported by an e-filing system, is an important factor in realizing the tax revenue target. The research aims to determine the effect of the e-filing system and taxpayer awareness on taxpayer compliance, and tax volunteers moderate the influence of the e-filing system and taxpayer awareness on taxpayer compliance. The method used is quantitative with primary data as a questionnaire with 100 taxpayer respondents in Serang City. Analysis uses the Structural Equation Modeling method with the help of SmartPLS 3.2.9 software The research results show that the e-filing system obtained a P-Value of 0.000<0.05, taxpayer awareness 0.031<0.05, tax volunteers did not moderate the influence of the e-filing system 0.691>0.05, and tax volunteers did not moderate the influence of taxpayer awareness 0.147>0.05. The conclusion of this research is that the E-Filing system and taxpayer awareness have a significant effect on taxpayer compliance, but tax volunteers do not moderate the influence of the e-filing system and tax volunteers do not moderate the influence of taxpayer awareness on taxpayer compliance